2022
DOI: 10.1108/ijem-09-2022-0339
|View full text |Cite
|
Sign up to set email alerts
|

Educational constellations: a systematic review of macro-networks in education

Abstract: PurposeNowadays, networks are the basic core of social organization and interaction; consequently, networking has become an indispensable requirement in today's societies. In education, the development of different types of collaborative networks has been observed, leading, in recent years, to the creation of educational macro-networks that generate links between schools and different types of institutions. Therefore, this study consists of a systematic review to examine the most relevant findings on this type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(225 reference statements)
0
0
0
Order By: Relevance
“…This concept was first applied in the United States and has widespread uses. Many countries promoted this concept to manage a substantial education system (Fernandez et al, 2023). In addition, the world change and the rapid growth of advanced technologies have affected human lifestyle and working in the 21 st century.…”
Section: Background and Significancementioning
confidence: 99%
“…This concept was first applied in the United States and has widespread uses. Many countries promoted this concept to manage a substantial education system (Fernandez et al, 2023). In addition, the world change and the rapid growth of advanced technologies have affected human lifestyle and working in the 21 st century.…”
Section: Background and Significancementioning
confidence: 99%
“…The principal's strategy in trying to improve teacher performance in learning through fostering teacher abilities, teacher discipline, teacher motivation, creating harmonious situations, increasing teacher commitment, meeting teacher needs and teacher training (Khattab, 2018); (Somech & Wenderow, 2006). Principals must be mature and careful in determining policies related to the implementation of their leadership strategies to get effective and efficient results (Barrero-Fernández et al, 2023). Teachers need to look at reality, the demands of society for education which according to them must be able to meet the needs of life, so it is not surprising that there are still people who look cynically at teachers when the results they see are not in accordance with their wishes, because the teacher is someone who must be imitated and exemplified in the sense of the word Teacher is a person who has charisma or authority because teachers play an important role in improving the quality of schools at various levels in the education unit (Ali et al, 2022);(Schulz et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Principal supervision and teacher professionalism (Thuy, 2022); (Jomocan & Legaspi, 2021). The role of the principal as a supervisor has a positive, innovative, inspiring impact on teachers in developing their knowledge according to the rapid development of the times (Elizabeth A. Foreman & Michael S. Retallick, 2013); (Kurniawan, 2016); (Barrero-Fernández et al, 2023). Previous studies have shown that a leader can be seen as an adaptive individual by providing a time frame for giving direction, providing support, actively participating, or delegating responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly within the field of education, the establishment of collaborative networks has emerged as a driving force for transformative change, encompassing innovation, educational enhancement and professional growth. Moreover, these networks have proven to be pivotal in ensuring the survivability of educational systems during times of crises (Barrero-Fern andez et al, 2022). Furthermore, collaborative problem-solving, intervention with mutual support and collective action have become prevalent in modern educational systems (Harris et al, 2023).…”
Section: Introductionmentioning
confidence: 99%